Effect of production on reproduction - Edward P. Call (Kansas Agricultural Experiment Station Research Reports, 1987)
The genetic antagonsim that exists between production and reproduction is overcome by sound management practices. Kansas Holstein herds were ranked by quartile and analyzed by comparing various reproductive traits. Higher producing herds suffered less reproductive loss based upon the factors considered. The most significant differences concerned the average days dry, average days open on cows not yet serviced, percent of cows open more than 120 days since fresh, and average age at first calving. An adequate record system will identify potential reproductive problems, and a sound Preventive Herd Health Program (PHHP) will minimize actual losses from disease and cows not yet bred. All herds, regardless of production level, would benefit by calving heifers at 24 mo.; Dairy Day, 1987, Kansas State University, Manhattan, KS, 1987;
Keywords: Kansas Agricultural Experiment Station contribution; no. 88-114-S; Report of progress (Kansas Agricultural Experiment Station); 527; Dairy; Production; Reproduction